E-Learning Application Based on Learning Management System for Online Teaching Adaptation at State Vocational School - Saltanat Meiramova; Imran, Andi Ahmad Ali; Mansyur; Syahrul; Mahmud Mustapa; Ahmed J. Obaid (Ceddi Journal of Information System and Technology (JST), 2025)
The learning process at SMK Negeri 1 Bone (State Vocational High School 1 Bone) remains predominantly conventional, requiring physical interactions between teachers and students in the classroom. This limitation highlights the need for technological integration to enhance accessibility and flexibility in education. This study aims to design and implement an e-learning application based on a Learning Management System (LMS) to facilitate online learning adaptation at SMKN 1 Bone. The development follows the UML model, while system testing employs the black-box method. Data were collected through field research and literature reviews from various academic sources. The results of this study led to the development of an LMS-based e-learning application that significantly supports online learning implementation. A user effectiveness test involving 30 respondents yielded a 71.57% feasibility score, categorizing the system as viable. Furthermore, black-box testing confirmed the system's functional reliability. This research contributes to the global discourse on digital education by demonstrating the practical application of LMS technology in vocational education, offering insights into scalable solutions for enhancing learning accessibility and effectiveness worldwide.